THE IMPACT OF TOTAL MOISTURE AND ASH ON CALORIFIC VALUE: COAL RESEARCH IN BERAU SUB-BASIN, EAST KALIMANTAN - Sugiarto, Wahyu; Muljana, Budi; Syafri, Ildrem; Rizal, Yan; Prasetya, Muhammad Nurul Huda (Institut Teknologi Nasional Yogyakarta, 2025)
Coal quality is one of the key factors in determining the effectiveness of processing and utilization. Coal quality assessment involves analyzing physical and chemical aspects to determine its characteristics. Coal quality is also influenced by geological conditions at the mining site, which affect the quality and amount of carbon in the coal. To ensure consistency, it is necessary to implement coal quality control based on physical and chemical parameters from the mining process in the pit to storage in the stockpile. Analysis of the effect of total moisture and ash on the calorific value of coal is the purpose of this study. The method used is a ROM (Run of Mine) coal sample located at the stockpile location. The relationship between Total Moisture and the calorific value of coal shows a negative linear correlation where the influence value for a 1% increase in Total Moisture is -71.343 kcal/kg and so is between Ash and the calorific value of coal 1% increase in Ash is -82.588 kcal/kg, which shows a negative linear correlation. Total Moisture increases by 1%, reducing the calorific value of coal by 71 kcal/kg, and increasing Ash content by 1% reduces the calorific value of coal by 83 kcal/kg.